Knowledge and attitude towards infection control among supporting staffs of Chitwan Medical College, Bharatpur, Chitwan - Lopchan, M; Gurung, G; Rajbanshi, L; Osti, C; Baniya, A (Journal of Chitwan Medical College, 2017)
Nosocomial infections (NIs) are one of the most important health issues, particularly in developing countries, because these infections cause high mortality and morbidity, and economic and human resource loss as a consequence Nosocomial infections can be defined as those occurring within 48 hours of hospital admission, 3 days of discharge or 30 days of an operation. Many studies have examined risk factors of nosocomial infections. However, knowledge of frontline workers (attendants) in infection prevention have been reported rarely in developing countries. The aim of this study was to investigate the knowledge of attendants working in different wards and OPDs about infection prevention. S: Data were collected from 100 attendants in Chitwan Medical College Teaching Hospital. Regarding the knowledge on hand washing, gloving and personal accessories for Infection Prevention, majority of the respondents had good knowledge ranging from 94-100%. Though hospital has established Infection Prevention Committee and regular training on infection prevention is provided to all the staffs, the data indicated that only 68% respondents were benefitted by the infection prevention training and proper use of virex solution to disinfect the equipment’s was found unsatisfactory. Infection control is the responsibility of all Health Care Facility (HCF) personnel. The goal of the infection control policies are to identify and reduce risks of acquiring and transmitting infections among patients, staff, students, volunteers, contract service workers, and visitors Although significant effort has been made to reduce the Nosocomial infections, regular training as well as monitoring supervision will enhance the capacity of the health care providers and front line workers for cleaning services they are our valued respondents.DOI: http://dx.doi.org/10.3126/jcmc.v6i1.55069